Clino-suenoite, a newly approved magnesium-iron-manganese amphibole from Valmalenco, Sondrio, Italy. (28th February 2018) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank C.; Ciriotti, Marco E.; Revheim, Olav; Bracco, Roberto
ABSTRACT: Clino-suenoite, ideally □ ${\rm Mn}_{2}^{2 +} $ Mg5 Si8 O22 (OH)2 is a new amphibole of the magnesium-iron-manganese subgroup of the amphibole supergroup. The type specimen was found at the Lower Scerscen Glacier, Valmalenco, Sondrio, Italy, where it occurs in Mn-rich quartzite erratics containing braunite, rhodonite, spessartine, carbonates and various accessory minerals. The empirical formula derived from electron microprobe analysis and single-crystal structure refinement is: A Na0.04 B ( ${\rm Mn}_{1.58}^{2 +} $ Ca0.26 Na0.16 )Σ2.00 C (Mg4.21 ${\rm Mn}_{0. 61}^{2 +} {\rm Fe}_{0.04}^{2 +} $ Zn0.01 Ni0.01 ${\rm Fe}_{0.08}^{3 +} $ Al0.04 )Σ5.00 T Si8.00 O22 W [(OH1.94 F0.06 )]Σ=2.00. Clino-suenoite is biaxial (+), with α = 1.632(2), β = 1.644(2), γ = 1.664(2) and 2Vmeas. = 78(2)° and 2Vcalc. = 76.3°. The unit-cell parameters in the C2 / m space group are a = 9.6128(11), b = 18.073(2), c = 5.3073(6) Å, β = 102.825(2)° and V = 899.1(2) Å 3 with Z = 2. The strongest ten reflections in the powder X-ray diffraction pattern [ d (in Å), I, ( hkl )] are: 2.728, 100, (151); 2.513, 77, ( $\bar 2$ 02); 3.079, 62, (310); 8.321, 60, (110); 3.421, 54, (131); 2.603, 42, (061); 2.175, 42, (261); 3.253, 41, (240); 2.969, 40, (221); 9.036, 40, (020).